Exploring factors that influence child use of dental services and toothbrushing in New Zealand - Jamieson LM, Koopu PI. (Blackwell Synergy, 2006)
To explore factors contributing to dental service use and toothbrushing among Ma¨ori, Pacific and New Zealand European or Other (NZEO) children in New Zealand.